STUDI POLA ASUH ORANG TUA PADA PESERTA DIDIK KELAS XI SEKOLAH MENENGAH ATAS SWASTA TAMAN MULIA SUNGAI RAYA TAHUN AJARAN 2019/2020 - Oktavia Lorensa Krisno; Luhur Wicaksono; Purwanti Purwanti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe first education that children receive in their lives comes from their family, particularly their parents, and might take the shape of parenting, attitudes, or conduct demonstrated by parents toward their children in daily life. The researcher is looking into the Parenting Pattern for Class XI Students at Taman Mulia Sungai Raya Private High School in this case. The purpose of this study is to examine the parenting patterns of Taman Mulia Sungai Raya Private High School's class IX students. The research method is descriptive and quantitative, with a survey as the research form. This survey included 56 pupils from Taman Mulia Sungai Raya Private High School. Indirect communication approaches and data collection instruments including questionnaires were employed to obtain data. The % formula is used in the data analysis technique. According to the findings of this study, the overall Parenting Pattern achieves a percentage of 81 percent, placing it in the "High" category, parental control reaches a percentage of 85 percent, and parental behavior demands reach a percentage of 78 percent in the "High" category, In the "High" category, communication between parents and children received 79 percent of the vote, and parenting practices for children received 83 percent.Keywords: Parenting, Parents, and Students.